PENGUATAN KEBIJAKAN KELEMBAGAAN BADAN USAHA MILIK DESA DI DESA SUKA GERUNDI KECAMATAN PARINDU KABUPATEN SANGGAU - NIM. E1011151133, AGUNG WICHAKSONO PRABOWO (PublikA, Jurnal Ilmu Administrasi Negara, 2019)
Skripsi ini membahas tentang penguatan kebijakan kelembagaan Bumdes menuju Desa Mandiri di Desa Suka Gerundi Kecamatan Parindu Kabupaten Sanggau pada tahun 2019. Subyek pada penelitian ini adalah Kasi pengembangan ekonomi dan teknologi tepat guna Dinas Pemdes, tenaga ahli pengembangan ekonomi desa, Kepala Desa Suka Gerundi, direktur bumdes dan masyarakat desa. Tujuan dari penelitian ini adalah mengetahui bagaimana penguatan kebijakan kelembagaan desa menuju Desa mandiri di Desa Suka Gerundi Kecamatan Parindu Kabupaten Sanggau. Metode yang digunakan adalah metode kualitatif. Temuan dari penelitian ini menunjukan kebijakan kelembagaan bumdes yang ada di desa suka gerundi belum berjalan secara efektif menuju desa suka gerundi yang mandiri, dibuktikan dengan belum adanya produk unggulan desa dan masyarakat sekitar belum merasakan secara signifikan peningkatan perekonomian dengan hadirnya bumdes, serta partisipasi masyarakat yang belum secara maksimal diberdayakan untuk menciptakan iklim perekonomian desa yang aktif. Kesimpulan dari penelitian ini adalah kebijakan kelembagaan bumdes menuju desa mandiri belum berjalan secara optimal, perlu adanya kebijakan pendidikan terhadap manajer bumdes dan pendidikan serta pelatihan-pelatihan kepada anggota bumdes. partisipasi masyarakat yang belum berjalan efektif perlu adanya partisipasi masyarakat didalam tiga tahap bentuk partisipasi seperti perencanaan, pelaksanaan, dan pemanfaatan. Bumdes dibentuk belum efektif dan sesuai dengan tujuan serta esensi dari bumdes, masyarakat harus dijadikan aktor dalam menciptakan iklim perekonomian desa yang aktif diwadahi oleh bumdes. .Kata Kunci: Penguatan Kelembagaan, Bumdes, Desa MandiriSTRENGTHENING INSTITUSIONAL POLCIES OF VILLAGE-OWNED ENTERPRISES TOWARDS AN INDEPENDENT VILLAGE IN SUKA GERUNDI VILLAGE OF PARINDU SUB-DISTRICT OF SANGGAU REGENCY AGUNG WICHAKSONO PRABOWO NIM: E1011151138 Dr. H. Rusdiono, M.SI , Drs. Abdulrahim, M.SI Email: agungwichaksonoprabowo27@gmail.com 1. Student of Public Administration Study Program, Faculty of Social and Political Science, Tanjungpura University, Pontianak 2. Lecture of Public Admimistration Study Program, Faculty of Social and Political Science, Tanjungpura University, Pontianak Abstract This undergraduate thesis discusses the strengthening of the Village-owned Enterprises’ institusional policies towards an Independent Village in Suka Gerundi Village of Parindu Sub-District of Sanggau Regency in 2019. The subject of this study are the Head of Economic Development and Approprite Technology of the Village Government Office, village economic development expert, Suka Gerundi Village Head, director of Village-owned Enterprises and people of the Village. The aim of this study is to find out about the strengthening of the village institutional policies towards an independent village in Suka Gerundi Village of Parindu SubDistrict of Sanggau Regency. The method used is a qualitative method. The findigs of this study showed that the institutional poliece of village Village-owned Enterprise in Suka Gerundi Village have not been effectively implemented towards the independent Suka Gerundi Village, as evidenced by the absence of superior products from the village and surrounding communities who have not enjoyed a significant increase in the economy with the presence of Village-owned Enterprises, and the community participation that has not optimally been empowered to create an active village economic climate. The conclusion of this research is that the village-owned Enterprise’ institutional policies towards an Independent Village have not run optimally. It is necessary to have an education policy for the Village-owned Enterprises’ managers as well as education and training for members of the Villageowned Enterprice’ members; community participation that has not been effective yet needs community participation in three stages of participation such as planning, implementation and utilization. The Village-owned Enterprises that were established have not yet been effective and in accordance with the objective and essence of the Village-owned Enterprises; the community must be made actors in creating an active village economic climate facilitated by the Village-owned Enterprises. Keywords: Institutional Strenghening, Village-owned Enterprises Independet Village